2006
DOI: 10.1136/aim.24.3.103
|View full text |Cite
|
Sign up to set email alerts
|

Relief of Low Back Pain Immediately after Acupuncture Treatment – a Randomised, Placebo Controlled Trial

Abstract: Background The purpose of this study was to examine the immediate effect of single acupuncture stimulation to the most painful point in patients with low back pain. Method Arandomised, evaluator-blinded, sham controlled clinical trial was conducted in which 31 patients with low back pain were randomly allocated to either an acupuncture group (n=15) or a sham acupuncture group (n=16). Both acupuncture and sham acupuncture were performed at the most painful point on the lower back of the subjects. For the acupun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 15 publications
0
39
0
4
Order By: Relevance
“…For simplicity, each comparison was treated as an individual trial. Trials reported on the following categories of interventions: acupuncture (10 trials) [25,42,73,74,85,95,99,104,106,128], back school (2 trials) [11,28], behavioural (7 trials) [10,21,62,111,130,132,133], electrotherapy (20 trials) [8, 15, 25, 27, 37, 49-51, 54, 57, 63, 69, 76, 77, 89, 94, 107, 122, 137, 143], exercise (10 trials) [29,37,43,48,50,59,67,116,131,136], heatwrap therapy (2 trials) [109,110], insoles (1 trial) [127], magnets (1 trial) [33], massage (1 trial) [116], neuroreflexotherapy (1 trial) [93] [16,117,129]. Trial characteristics are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…For simplicity, each comparison was treated as an individual trial. Trials reported on the following categories of interventions: acupuncture (10 trials) [25,42,73,74,85,95,99,104,106,128], back school (2 trials) [11,28], behavioural (7 trials) [10,21,62,111,130,132,133], electrotherapy (20 trials) [8, 15, 25, 27, 37, 49-51, 54, 57, 63, 69, 76, 77, 89, 94, 107, 122, 137, 143], exercise (10 trials) [29,37,43,48,50,59,67,116,131,136], heatwrap therapy (2 trials) [109,110], insoles (1 trial) [127], magnets (1 trial) [33], massage (1 trial) [116], neuroreflexotherapy (1 trial) [93] [16,117,129]. Trial characteristics are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Thanks for this very helpful note, the faulty citation is very unpleasant for us and we would like to correct this herewith. The correct citations in the section BStatistical analysis^are the ones mentioned above by Inoue [3] and Itou [4].…”
Section: Dear Editormentioning
confidence: 98%
“…In our paper, we present the original sample size calculation as done for the study protocol. This calculation of the number of cases is based on the work of Inoue [3] and Itou [4]. However, according to the pilot character of the study after the end of the intervention phase, we revised our strategy for data analyses based on the large number of measurements over time and the additional 3-month follow-up.…”
Section: Dear Editormentioning
confidence: 99%
“…Several studies have shown that acupuncture can be a useful modality for treating pain due to muscle spasms (Lundeberg et al, 1988: Sandberg et al, 2005: Inoue et al, 2006. It is believed that shoulder stiffness is caused primarily by restriction of blood flow to the working muscles where accumulated metabolites appear to activate sympathetic vasoconstrictors.…”
Section: Introductionmentioning
confidence: 99%